Solar System Game For Children’s Learning - Muhammad Zarith Aidid, Che Zakaria (2023)
An engaging 2D platformer game with a heavy focus on our solar system as its central theme, the Solar System Game Application is made for kids between the ages of 7 and 12. The game, which was created as an application for smartphones, gives players the freedom to interact with the educational material whenever and wherever they like. The main goal is to speed up the process of education and assist young players in building a strong knowledge base regarding the solar system. The game seeks to offer a deeply engaging experience that sparks interest and encourages an awareness of the celestial bodies in our solar system through interactive gameplay, educational material, and user-friendly features. In order to assure the game's instructional effectiveness, the project makes use of the RAD (Rapid Application Development) methodology, which enables effective creation and iterative changes. The project's outcomes show how an entertaining and informative 2D quiz game was successfully created, allowing young players to acquire a fundamental knowledge of our solar system in a fun and engaging manner.